A new recombinant thrombolytic and antithrombotic agent with higher fibrin affinity – a staphylokinase variant - Szemraj, Janusz; Stankiewicz, Adrian; Rozmyslowicz-Szermńska, Wioletta; Mogielnicki, Andrzej; Gromotowicz, Anna; Buczko, Wlodzimierz; Oszajca, Katarzyna; Bartkowiak, Jacek; Chabielska, Ewa (Thrombosis and Haemostasis, 2007)
The recombinant protein SAK-RGD-K2-Hir is characterized by its fibrin-specific properties of plasminogen activation combined with antithrombin and antiplatelet activities. It was previously shown in our in-vitro studies to be a more potent and faster-acting thrombolytic agent compared with standard r-SAK. In order to document the effects of the thrombolytic potential of SAKRGD- K2-Hir we examined this protein in an electrically induced carotid artery thrombosis model and stasis-induced venous model in rats. In the arterial thrombosis model, a bolus injection of SAK-RGD-K2-Hir was less effective than rt-PA and r-SAK. However, the most effective in the improvement and maintenance of carotid patency and in arterial thrombus mass reduction was SAK-RGD-K2. In contrast, all r-SAK derivatives reduced venous thrombus weight significantly in comparison to r-SAK and r-Hir. However, the most observable decrease in thrombus weight was obtained after application of recombinant proteins containing the r-Hir.The bleeding time was significantly prolonged in the animals treated with proteins containing r-Hir at a dose of 1.0 mg/kg.There were no observable changes in plasma fibrinogen concentration.In conclusion,our findings show thrombolytic activity in intravenous bolus injection of the novel thrombolytic agent SAK-RGD-K2-Hir in rats.Although this protein compares favourably with r-SAK in rat venous thrombolysis, we were unable to confirm the beneficial effects of SAK-RGDK2- Hir over r-SAK and rt-PA in the carotid artery thrombolysis model. Furthermore, our results also suggest that SAKRGD- K2-Hir bears a risk of bleeding, but this may be true for higher doses.
Keywords: Recombinant protein; antiplatelet activity; thrombolytic agent; arterial thrombosis; venous thrombosis